Discrimination against women in film “Gadis Kretek” - Narti, Sri; Syaputra, Dery; Yanto, Yanto (The International Journal of Politics and Sociology Research, 2024)
The film "Gadis Kretek" highlights the issue of discrimination against women. This analysis employs Roland Barthes' semiotic approach to dissect how signs and symbols in the film reflect social realities. The film presents an engaging narrative that mirrors the social dynamics, particularly concerning gender roles in the kretek industry. Using a qualitative method with a critical paradigm, data were collected through observation and documentation, and analyzed using Barthes' semiotic technique, focusing on denotative, connotative, and mythic signs. The denotative analysis highlights the facial expressions of female characters, dialogues, and the depiction of women in the kretek factory environment. The connotative analysis examines visual and narrative symbols portraying the limited roles of women in society at that time, through elements such as clothing colors, specific symbols, and scene layouts. The mythic analysis addresses societal stereotypes and beliefs about women's roles in the tobacco industry, as well as the film's efforts to challenge these views. The findings indicate that "Gadis Kretek" successfully depicts the complex social reality surrounding women's roles in the kretek industry, including discrimination and stereotypes that are still relevant today. Through semiotic analysis, the film provides a profound insight into inequality, role limitations, and women's struggle against patriarchal norms. These insights contribute to understanding how films can serve as tools for conveying social messages and highlighting issues of gender discrimination. "Gadis Kretek" not only entertains but also educates its audience on the ongoing issues of gender inequality, making it a significant work in both cinematic and social contexts.